PENGARUH PROSES PRODUKSI DAN PENGEMASAN TERHADAP MINAT BELI PRODUK “BUBUK SOKLA” - Arij Rosa Indah; Vita Kurnia Utami; Ach Haris Abdi Manaf (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Sumenep is one of the districts on Madura Island which is classified as a region producing traditional herbal medicine, one of which is Sokla powder. Sokla powder is a traditional herbal medicine made from several types of herbal plants such as ginger, turmeric, etc. Making sokla powder itself is a production activity using certain TOGA carried out by the Kasih Ibu Farming Women's Group (KWT) in Lengkong Bragung Village, Guluk-Guluk, Sumenep. The production activity referred to in this case is an activity to increase the added value of an item by involving several production factors together. Meanwhile, product packaging not only functions as a container for wrapping food or beverage products to protect them from dirt, dust, air, impact and sunlight, but also as a promotional tool to attract buyers' interest. The aim of this research is to determine the influence of the production and packaging process on purchasing interest in sokla powder products. The method used in this research is descriptive quantitative, while the data processed is using the SPSS version 26 program. Data was obtained from distributing questionnaires to 50 respondents. The results obtained from this research show that the production and packaging process variables do not have a partial and significant effect on purchase interest, with the results of the t test where the calculated t of the two variables is X1=1.830 and X2=-1.412 < t table 2, 011 obtained from a significance level of 5% and df=50-2- 1. Meanwhile, simultaneously the calculated F value obtained is 2.036 < f table of 3.20, which means that the production and packaging processes have no simultaneous and significant influence on purchasing interest.